Data acquisition based on vehicular cloud. Issue 6 (1st November 2018) - Dou, Zhengxiong; Wang, Xiaonan; Li, Yanli
Abstract : With technological advancements, vehicles are equipped with abundant storage capability and powerful computing capability. This leads to an advanced kind of vehicular ad hoc network service, which enables local collaborations among vehicles to produce service data an individual cannot make alone. To support this advanced service, a vehicular cloud (VC) is proposed. One VC usually adopts flooding to acquire data, so the data acquisition cost is relatively high. To reduce the cost, the authors employ the address‐based unicast to achieve data acquisition and propose a data acquisition method based on address‐based VC. In this method, the unicast address and data address are proposed to establish a relationship between one kind of specific data and an address. On the basis of the data address, a vehicle can retrieve data from the nearest VC member in the unicast way, so the data acquisition cost is reduced. This proposal is evaluated, and the data show that the data acquisition cost is effectively reduced.